1967
DOI: 10.1099/00221287-47-1-103
|View full text |Cite
|
Sign up to set email alerts
|

The Growth of Mycoplasma bovigenitalium in Cell Cultures

Abstract: SUMMARYA strain of Mycoplasma bovigenitalium, designated M 120, was grown, and produced a marked cytopathic effect (c.p.e.) in calf-, pig-, and monkeykidney cell cultures. The c.p.e. was characterized by enlargement of the cells, the appearance of intracytoplasmic inclusions and partial destruction of the cell monolayers. A similar c.p.e. was produced in tissue-culture cells following the inoculation of mycoplasma 'toxins'.Comparative growth studies of strain M 120 in calf-kidney cell cultures and in tissue-cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1970
1970
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…L-Arginine deficiency of the culture fluid has been reported as the cause of CPE of some strains of mycoplasma (21,22,30). Additional L-arginine failed to prevent-the C-PE of the Donetta organism, and similar findings have been reported for other species of mycoplasma (1,8).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…L-Arginine deficiency of the culture fluid has been reported as the cause of CPE of some strains of mycoplasma (21,22,30). Additional L-arginine failed to prevent-the C-PE of the Donetta organism, and similar findings have been reported for other species of mycoplasma (1,8).…”
Section: Discussionsupporting
confidence: 87%
“…Cell culture fluid from monolayers exhibiting advanced CPE would not produce changes in other cell cultures after the fluid was treated with broad-spectrum antibiotics (32). These results suggest that the CPE were not due to a soluble toxin and that the cause is probably different from that of another bovine mycoplasma (1).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The effects of mycoplasmas on the morphology of contaminated cell lines range from zero (26,135,155,156) to increase in cytoplasmic granularity and retardation of growth (91,185,186) to frank cytopathology (3,9,24,27,54,61,66,76,84,88,137,185,186). The mycoplasmas may have such a drastic effect upon the cell cultures that the whole cell population lyses (92, 94).…”
Section: Mycoplasma Effects On Cell Growth and Morphology Morphologymentioning
confidence: 99%
“…Their work also found evidence that the collodion bag released a mycoplasma-produced component that induced necrosis in the surrounding tissues and might have contributed to cachexia in the rabbit (Lloyd, 1966). Other studies in the 1960s-1970s demonstrated some cellfree molecules released by mycoplasmas, such as polysaccharides or antigens recovered from the body fluids of CBPP-infected animals (Plackett et al, 1963;Gourlay, 1965), nanosized globular elements observed by microscopy in M. pneumoniae broth cultures (Eng and Froholm, 1971), and uncharacterized molecules that had cytotoxic activity in the supernatant of M. bovigenitalium cultures (Afshar, 1967). However, investigators at the time were unable to precisely identify the chemical structure of these elements, as they were unable to purify them from components of the complex growth medium or from body fluids.…”
Section: Introductionmentioning
confidence: 98%